Structure of Arthropoda Community in an Orange Orchard with Conventional Systems in Bedengan, Dau, Malang - El Fikri, Galih; Yanuwiadi, Bagyo; Gama, Zulfaidah Penata (Proceeding International Conference on Global Resource Conservation, 2015)
Citrus is a major commodity in Malang. Pests attack can reduce yields of citrus. Farmers reduce pests by pesticides. The presence of pesticides would reduce biodiversity so as to cause an imbalance in the system of the chain food. It is necessary to identify the abundance and diversity of species in an orange orchard with conventional systems. The purpose of this study is to identify the structure of arthropod community and determine the stability of the environment in citrus orchards with conventional systems. This study was conducted in April 2015 - January 2016 in an orange orchard with conventional systems in Bedengan, Dau, Malang. Sampling was done in three times by the method of pitfall traps and yellow trap. Each sample has two treatments, before spraying and after spraying to determine differences in the structure of arthropod community. Results have shown that there are differences in arthropod diversity between two different places. There are some species that are dominant in each of these places. Comparison of diversity between the two places is more significant than the before and after spraying. Order of insects with the largest number of individuals is of the order Diptera 671 individuals. 440 individuals and the order Coleoptera order Hymenoptera 133. The family Formicidae before spraying has a value of 33.38 and 43.20 after spraying. And in orchard2 important value index score was 21.86 and the family Formicidae 21.91, family Culicidae 30.95 and 23.64. And in orchard2 69.52 and 24.01. family Drosopilidae 41.47 and 43.20. While in orchard2 has a value of 30.18 and 59.10. There are differences in diversity between before and after spraying spraying. Animal diversity could rise or fall depending on the behavior of each species.Keywords: Arthropods; citrus orchards with conventional systems; pitfall trap; yellow trap